Perbandingan Teknis Penyemprotan Gulma secara Manual dan Menggunakan Drone Sprayer di Lahan Replanting - Mahhendra, Danang Wasis; Mawandha, Hangger Gahara; Yuniasih, Betti (Program Studi Agroteknologi INSTIPER, 2024)
Weed control during replanting activities is an important activity. In general, weed control was done using a knapsack sprayer, but currently weed control can also be done using a drone sprayer. This research was conducted to compare the effectiveness and efficiency of weed control using knapsack sprayers and drone sprayers. This research compares the application of knapsack sprayers and drone sprayers in controlling weeds during replanting of oil palm plantations which includes the time required for the weeds to die, the duration of time required for spraying, and the costs required. The data obtained were analyzed using the independent T test. The results of the research show that using a drone sprayer to control weeds during replanting is more efficient in terms of time and cost than using a knapsack sprayer, while in terms of effectiveness in killing weeds there is no real difference between both. Drone sprayers provide a better alternative for weed control when replanting in oil palm plantations.